Non-linear seismic behavior of historic Adana Great Clock Tower - Erkek, Hakan; Calayir, Yusuf; Yetkin, Musa (Elsevier Science Inc, 2024)
In this study, the non-linear seismic behavior of the historic Adana Great Clock Tower was investigated. The dynamic characteristics (natural frequencies and mode shapes) of the Clock Tower were determined by operational vibration tests. The finite element model of the Clock Tower was manually updated in the light of the experimentally obtained dynamic characteristics. For the updated finite element model, pushover analyses and non-linear time history analyses were performed. Incremental pushover analyses were performed in the x and y directions proportional to the first lateral displacement modes of the Clock Tower in the x and y directions. The time history analyses took into account the Adana-Ceyhan (1998) earthquake acceleration records. Each of the two horizontal components of the earthquake acceleration records was separately scaled according to the design spectrum defined in TBEC-2018 for earthquake levels with a 10 % and 50 % probability of exceedance in 50 years. These scaled earthquake acceleration records were applied to the structure. The two scaled horizontal components for the same earthquake level were rotated 90 degrees and reapplied to the structure. As the response quantities, displacement, base shear force and plastic strains were evaluated.
Keywords: Model updating; Historical clock tower; Dynamic characteristics; Non-linear seismic behavior